Peran Nilai-Nilai Ajaran Buddha dalam Menanggapi Permasalahan Sosial Kemasyarakatan - Rusmiyati Rusmiyati; Tripitoyo Tripitoyo; Kabri Kabri; Partono Nyana Suryanadi (Jurnal Budi Pekerti Agama Buddha, 2025)
Buddhist teachings play a crucial role in addressing various social problems that continue to develop in the modern era. Rapid social change, globalization, and technological advancement have brought not only positive impacts but also serious challenges, such as increasing social conflicts, moral degradation, individualism, and the weakening of social awareness within society. In this context, Buddhism offers universal ethical guidance that remains relevant across time, particularly through the principles of compassion (karuṇā), loving-kindness (mettā), wisdom (paññā), and mental equanimity (upekkhā), which guide individuals toward harmonious and responsible living. This study aims to analyze the role of Buddhist values in providing solutions to contemporary social problems. The research employs a descriptive qualitative method based on library research, using a hermeneutic approach to Buddhist sacred texts and relevant scientific studies. The findings indicate that the application of Buddhist values contributes significantly to the development of social morality, the strengthening of social solidarity, conflict resolution, and the formation of individual character marked by empathy, tolerance, and responsibility. Furthermore, these values play an essential role in fostering interreligious harmony and cultivating collective awareness of the importance of peaceful coexistence within pluralistic and multicultural societies.